Absence of macrophage migration inhibitory factor reduces proliferative retinopathy in a mouse model - Wang, Jing; Lin, Jihong; Kaiser, Ulrike; Hammes, Hans-Peter (Acta diabetologica, 2017)
AimsIschemia-induced neovascularization is the key feature of proliferative diabetic retinopathy. Macrophage migration inhibitory factor (MIF) is a pleiotropic proinflammatory and proangiogenic cytokine, and its levels are elevated in the vitreous of patients with proliferative diabetic retinopathy. In this study, we aimed at investigating the relative potential of MIF in the ischemia-induced retinal neovascularization.MethodsBoth WT and MIF-knockout mice were subjected to the retinopathy of prematurity (ROP) model. Intraretinal vessel regrowth was assessed by whole-mount immunofluorescence, and preretinal neovascularization was analyzed in retinal vertical sections after periodic acid-Schiff staining in the hypoxic stage of the ROP model. Gene expression of selected proangiogenic and proinflammatory factors at postnatal day 13 (p13) was measured by real-time PCR. Vascular endothelial growth factor (VEGF) expression, recruitment of endothelial progenitor cells (EPCs) and microglial activation were analyzed with immunofluorescence.ResultsMIF deficiency increased areas of vascular obliteration by 49%, reduced sprouting tips by 27% and inhibited preretinal angiogenesis by 35%. VEGF expression was reduced in Müller cells of MIF-knockout mice. MIF absence reduced gene expression of erythropoietin, tumor necrosis factor alpha and intercellular adhesion molecule-1 by 30, 70 and 50%, respectively, decreased the number of retinal EPCs by 37.5% and inhibited microglial activation in the hypoxic condition.ConclusionsIn conclusion, we found that MIF has proangiogenic and proinflammatory properties in retinal neovascularization. The proangiogenic role of MIF in ischemia-induced retinal neovascularization is associated with the expression of VEGF and erythropoietin, EPC recruitment and inflammation. Therefore, MIF has a potential role in the pathological angiogenesis of proliferative retinopathy.